Students’ Perceptions and Attitudes towards the Utilization of Duolingo in EFL Learning - Ira Irzawati; Agnes Felisya Unamo (UIR Press, 2023)
Education sector in the 21st Century has continuously changed and relied more on technology. The evolution of the use of technology in education leads to the emergence of gamification. Duolingo is a language learning platform that provides free language courses through web and mobile apps that instills gamification aspects. The objective of this study is to investigate the students’ perceptions and attitudes towards the utilization of Duolingo in EFL learning. This descriptive study involved twenty students of a non-English education study program through purposive sampling technique. The criteria of selecting the participants were based on the participation in English Learning class and the active use Duolingo for English practice outside the course hours. The researchers employed a questionnaire and an interview to collect the data. The data of the questionnaire were analyzed quantitatively through simple percentage analysis of SPSS. Meanwhile, the data of the interview were analyzed qualitatively through Miles, et al. Model consisting of collection, classification, description, interpretation, and conclusion. The results revealed that the students provided positive feedbacks towards thirty statements of questionnaire and three questions of interview that representing their perceptions and attitudes towards the utilization of Duolingo in EFL learning. The students believed that learning English through Duolingo was easy, fun, engaging, and motivating. In short, the students had positive perceptions and attitudes towards the utilization of Duolingo in EFL learning.